Bidirectional Relationships among Children's Perceived Competence, Motor Skill Competence, Physical Activity, and Cardiorespiratory Fitness across One School Year. (27th August 2021) - Ryu, Suryeon; Lee, Jung Eun; Zeng, Nan; Stodden, David; McDonough, Daniel J.; Liu, Wenxi; Gao, Zan
Abstract : Purpose . The bidirectional associations among children's motor skill competence (MSC), perceived competence (PC), physical activity (PA), and cardiorespiratory fitness (CRF) over time remain unanswered. This study is aimed at discerning the bidirectional relationships among elementary school children's MSC, PC, PA and, CRF over the course of one school year. Methods . A total of 261 second and third grade children (127 boys, 134 girls; mea n age = 8.27 years; BMI = 18.22 ± 3.71 ) were recruited from two Texas elementary schools. Approximately 73.56% of participants were White American. Children's baseline data were assessed in September/October in 2012 (Time1), and identical assessments were conducted in April/May in 2013 (Time2). MSC was assessed using product-oriented skill tests (e.g., throw, kick, and jump). PC was assessed via the Pictorial Scale of Perceived Competence for Children. Minutes spent in moderate-to-vigorous PA (MVPA) was assessed using ActiGraph GT3X+ accelerometers for five days, and CRF was assessed by the PACER test. Six age- and body mass index-adjusted cross-lagged panel models were used to test the relationships between the variables. Results . We observed that T1 MSC significantly predicted T2 MSC (β = 0.59 ; p < 0.01 ), T2 CRF (β = 0.28 ; p < 0.01 ), and T2 MVPA (β = 0.18 ; p < 0.01 ). Children's CRF was a positive predictor for T2 CRF (β = 0.56 ; p < 0.01 ) and T2 MSC (β = 0.13 ; p < 0.05 ) Additionally, T1 MVPA significantly predicted T2 MVPA (β = 0.30 ; p < 0.01 ) and T2 PC (β = − 0.14 ; p < 0.05 ). Conclusion . Findings suggested a fully bidirectional relationship between elementary children's MSC and CRF. Other bidirectional relationships among the variables were only partially supported. Educators and health professionals need to emphasize the importance of developing both MSC and CRF to maintain physical health over time.